Classification of compliments as speech acts and their basic characteristics in Uzbek and English languages - Sadikov Erkin Tursunovich (Genius Journals, 2022)
This paper aims to investigate and compare the notions and scientific angles of scholars by illustrating the specific features of speech acts of compliments. Primarily, it decodes elements and types of components; secondly, the work combines compliments with other speech acts and distinguishes some relations among them. Finally, this research presents a clear criterion which supports both teachers and learners identify the classification of compliments in Uzbek and English languages.
Keywords: Speech Acts; Compliments; Conversation; Provision